IMPLEMENTASI LAYANAN KONSELING DALAM MENGATASI KEKERASAN TERHADAP ANAK: STUDI LITERATUR - Hanifah, Nur; Stefani, Savina Anindita; Setyo Budy, Muhammad Hanif; Adnan, Lutfiyana Hisyam (Universitas PGRI Semarang, 2023)
Violence against children is an urgent issue in society, potentially causing long-term impacts both physically and psychologically. This study aims to determine the implementation of counseling services in overcoming violence against children. The method used is a literature review by collecting data from various journal articles. The results of this study indicate that counseling services are effective in reducing acts of violence against children and improving children's psychological well-being. The conclusion of this study is that counseling efforts in handling violence against children include psychological trauma recovery, family strengthening, and child protection advocacy. The techniques used vary, such as family therapy, individual and group counseling, and religious values-based approaches. The results showed a decrease in trauma and aggressive behavior, as well as an increase in self-confidence. Thus, counseling services are effective in improving children's psychological well-being.Keywords: Child abuse; counseling services; psychological well-being.